Investigating the relation between positive affective responses and exercise instigation habits in an affect-based intervention for exercise trainers: A longitudinal field study - Weyland, Susanne; Fritsch, Julian; Feil, Katharina; Jekauc, Darko (Frontiers in Psychology, 2022)
The present study contains an affect-based intervention intended to support exercise trainers in positively influencing their course participants’ affective responses to their exercise courses. We argue that positive affective responses are associated with habit formation, thereby being a promising approach for avoiding high drop-out rates in exercise courses. First, the present study aimed to investigate whether the intervention for exercise trainers could increase a) affective attitudes, and b) exercise instigation habit strength, and influence the development of c) weekly measured affective responses and d) automaticity among adult participants of exercise courses. Second, it examined the relationship between the development of affective responses and exercise instigation habit strength. Ten exercise trainers of weekly sports and exercise courses at a German university received either an affect-based intervention or a control intervention. 132 of their course participants answered the Self-Report Habit Index (SRHI; the automaticity sub-scale SRBAI was also analyzed) for exercise instigation habit strength and items to measure affective attitude in the initial and final assessment. Moreover, they were assessed for a duration of 10 weeks during which, each time after attending the course, they reported their affective response to exercise as well as their automaticity in arriving at the decision to exercise. In the repeated measures ANOVA, there was a significant main effect of time for exercise instigation habit strength. Overall, habit strength was higher in the final than in the initial assessment. However, there were no significant differences between the two conditions in all study variables. In the latent growth curve model, the trajectory of the latent growth curve of valence was a significant predictor of the final exercise instigation habit strength. While the applied affect-based intervention was not successful in enhancing positive affective responses to exercise, the results indicate that positive affective responses may contribute to strengthening exercise instigation habits. Future studies should examine the effectiveness of interventions in long-term study designs.